Dependence of Tractor Traction Properties on Agricultural Machinery Connections - G. A. Iovlev; I. I. Goldina (Сельскохозяйственные машины и технологии)
Tractor traction properties depend on many factors including engine power, operating weight and tractor weight distribution across axles, dimensions, profile, gears range and gear count in the gearbox. Moreover, the tractor technical condition plays a vital role, encompassing aspects from the fuel system affecting the engine power output, to the chassis, influencing terrain traversability, maneuverability, and soil deformation. (Research purpose) The paper addresses several research problems. To investigate the impact of the agricultural machinery connections with the tractor on the tractor traction properties, and determine the impact of agricultural machinery weight, and grip width on the main technical and economic parameters. To analyze how geometrical parameters of tractors and agricultural machinery correlate with soil reactions under the machine support wheels as well as the front and rear wheels of the tractor. To determine the influence of the design characteristics of cultivators with varying working widths on the main operational properties of the machine-tractor unit. (Materials and methods) The study involves examining the operation of the Belarus 82.1 tractor with cultivators KPS-4 and KPS-5 from different manufacturers. Various methods were employed, including calculation, calculation-construction, calculation-graphic analysis, economic-mathematical techniques, along with comparison, measurement, and description. (Results and discussion) This study identified indicators impacting the load redistribution transmitted to the tractor from mounted cultivators. Based on these indicators, alterations in soil reactions under cultivator support wheels and the tractor’s rear wheels were deduced. (Conclusions) The calculations on the effect of mounted cultivators with different working widths (different operating weight) on the redistribution of soil reactions between axles, enabled the determination of modifications in tractor traction force, machine-tractor unit productivity, and specific fuel consumption.